Transcription Factor DOF4.1 Regulates Seed Longevity in Arabidopsis via Seed Permeability and Modulation of Seed Storage Protein Accumulation - Niñoles, Regina; Ruiz-Pastor, Carmen Maria; Arjona-Mudarra, Paloma; Casañ, Jose; Renard, Joan; Bueso, Eduardo; Mateos, Ruben; Serrano, Ramón; Gadea, Jose (Frontiers in Plant Science, 2022)
Seed longevity is modulated by multiple genetic factors in Arabidopsis thaliana. A previous genome-wide association study using the Elevated Partial Pressure of Oxygen (EPPO) ageing assay pinpointed a genetic locus associated with this trait. Reverse genetics identified the transcription factor DOF4.1 as a novel seed longevity factor. dof4.1 loss-of-function plants generate seeds exhibiting higher germination after accelerated ageing assays. DOF4.1 is expressed during seed development and RNAseq data show several putative factors that could contribute to the dof4.1 seed longevity phenotype. dof4.1 has reduced seed permeability and a higher levels of seed storage proteins mRNAs (cruciferins and napins) in developing seeds, as compared to wild-type seeds. It has been reported that mutant lines defective in cruciferins or napins present reduced seed longevity. The improved longevity of dof4.1 is totally lost in the quadruple mutant dof4.1 cra crb crc, but not in a dof4.1 line depleted of napins, suggesting a prominent role for cruciferins in this process. Moreover, a negative regulation of DOF4.1 expression by the transcription factor DOF1.8 is suggested by co-inoculation assays in Nicotiana benthamiana. Indeed, DOF1.8 expression anticorrelates with that of DOF4.1 during seed development. In summary, modulation of DOF4.1 levels during seed development contributes to regulate seed longevity.